2020
DOI: 10.3389/fpls.2019.01691
|View full text |Cite
|
Sign up to set email alerts
|

Potential of the C Genome of the Different Variants of Brassica oleracea for Heterosis in Spring B. napus Canola

Abstract: The genetic base of Brassica napus canola need to be broadened for exploitation of heterosis at a greater level in the breeding of F 1 hybrid canola cultivars. In this study, we evaluated 228 inbred B. napus canola lines derived from six B. napus × B. oleracea interspecific crosses and following two breeding methods (F 2-and BC 1-derived lines) to understand the effect of the B. oleracea alleles on heterosis for different agronomic and seed quality traits. Test hybrids of the inbreds derived from crosses invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Earlier at the end of the twentieth century, some studies have used RFLP and SSR markers to study the relationship between GD and heterosis, and proposed that the relationship between GD and heterosis could be predicted by genetic differences [ 17 ]. Subsequently, a number of studies used RAPD [ 18 ], AFLP [ 19 , 20 ], SSR [ 21 23 ], EST-SSR [ 24 , 25 ], insertion-deletion (InDel) [ 11 ] and SNP markers [ 13 , 26 – 28 ] to study the relationship between GD and heterosis. Previous studies used different molecular marker types and those results were also different, but the GD was not compared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier at the end of the twentieth century, some studies have used RFLP and SSR markers to study the relationship between GD and heterosis, and proposed that the relationship between GD and heterosis could be predicted by genetic differences [ 17 ]. Subsequently, a number of studies used RAPD [ 18 ], AFLP [ 19 , 20 ], SSR [ 21 23 ], EST-SSR [ 24 , 25 ], insertion-deletion (InDel) [ 11 ] and SNP markers [ 13 , 26 – 28 ] to study the relationship between GD and heterosis. Previous studies used different molecular marker types and those results were also different, but the GD was not compared.…”
Section: Discussionmentioning
confidence: 99%
“…In pearl millet, moderate positive significant correlations were found between GD and MPH for grain yield ( r = 0.37, p < 0.01) and BPH for grain yield ( r = 0.33, p < 0.01), respectively [ 21 ]. Nikzad et al found a positive correlation for the genetic distance of the inbred lines from the common Brassica napus parent with MPH for seed yield ( r = 0.31) and hybrid yield ( r = 0.26) [ 23 ]. Significant correlation was observed between GD and MPH of plant height, gross plant weight, net curd weight, leaf width, curd diameter and total marketable yield in Brassica oleracea [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In pearl millet, moderate positive signi cant correlations were found between GD and MPH for grain yield (r = 0.37, p < 0.01) and BPH for grain yield (r = 0.33, p < 0.01), respectively [21]. Nikzad et al found a positive correlation for the genetic distance of the inbred lines from the common Brassica napus parent with MPH for seed yield (r = 0.31) and hybrid yield (r = 0.26) [23]. Signi cant correlation was observed between GD and MPH of plant height, gross plant weight, net curd weight, leaf width, curd diameter and total marketable yield in Brassica oleracea [25].…”
Section: Genetic Distance Between Parents Assessed By Ssr and Snp Marmentioning
confidence: 99%
“…Earlier at the end of the 20th century, some studies have used RFLP and SSR markers to study the relationship between GD and heterosis, and proposed that the relationship between GD and heterosis could be predicted by genetic differences [17]. Subsequently, a number of studies used RAPD [18], AFLP [19,20], SSR [21][22][23], EST-SSR [24,25], InDel [11] and SNP markers [13,[26][27][28] to study the relationship between GD and heterosis. Previous studies used different molecular marker types and those results were also different, but the GD was not compared.…”
Section: Genetic Distance Between Parents Assessed By Ssr and Snp Marmentioning
confidence: 99%
“…Moreover, for combating biofuel consumption and climatic change challenges oilseed rape is getting popularity as a biodiesel crop. It is estimated that substantial demand in oilseed crops would be increased many-folds in near future (FAO 2002, Nikzad et al 2020.…”
Section: Introductionmentioning
confidence: 99%